Survey of the implementation of the recommendations in the Health Services Circular 1998/224 'Better Blood Transfusion'. - Murphy, M; Edbury, C; Wickenden, C (2003)
This report describes a questionnaire survey on the implementation of the recommendations of the Health Services Circular (HSC) 'Better Blood Transfusion' 1998/224 for improving transfusion practice. The survey was carried out to inform a second UK Chief Medical Officers' symposium on 'Better Blood Transfusion' in October 2001. Sixty-nine percent of hospitals where blood is transfused in England participated. The results show that, by 2001, most hospitals had established Hospital Transfusion Committees (HTCs), developed protocols for the process of transfusion and were participating in the Serious Hazards of Transfusion (SHOT) scheme. However, there was limited compliance with other recommendations, including the provision of training for staff involved in transfusion and information to patients, the development of protocols for the appropriate use of blood, the performance of audits of transfusion practice and the introduction of peri-operative cell salvage. The survey did not determine the reasons for this limited compliance. New initiatives including the issue of a further HSC on 'Better Blood Transfusion' are aimed at enabling hospitals to improve their transfusion practice in a more systematic way than that was found in the results of this survey.